2018
DOI: 10.1177/1071100718759966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankle Position on Tibiotalar Motion With Screw Fixation of the Distal Tibiofibular Syndesmosis in a Fracture Model

Abstract: Our findings suggest that maximal dorsiflexion during syndesmotic screw fixation may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…According to a previous classic study, plantarflexion of the ankle during syndesmotic screw placement leads to a decrease in dorsiflexion capacity 24 . However, other authors argued that there was no need to keep the ankle in maximal dorsiflexion when inserting the screw because they observed no significant relationship between the change in maximal dorsiflexion and ankle position 25 . van Zuuren et al 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous classic study, plantarflexion of the ankle during syndesmotic screw placement leads to a decrease in dorsiflexion capacity 24 . However, other authors argued that there was no need to keep the ankle in maximal dorsiflexion when inserting the screw because they observed no significant relationship between the change in maximal dorsiflexion and ankle position 25 . van Zuuren et al 2 .…”
Section: Discussionmentioning
confidence: 99%
“…24 However, other authors argued that there was no need to keep the ankle in maximal dorsiflexion when inserting the screw because they observed no significant relationship between the change in maximal dorsiflexion and ankle position. 25 van Zuuren et al 2 concluded that the most important aspect of syndesmotic fixation was the anatomical reduction of the syndesmosis and the ankle's position during fixation was ultimately not important. Therefore, further research is required to examine this question.…”
Section: Restrictions In Range Of Motionmentioning
confidence: 99%
“…However, in later cadaver studies, it was shown that ankle position during fixation did not affect motion. [ 26 ] Orthopedic surgeons are still confused between the previous and relatively new evidences.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,14 However, several complications of screw fixation, such as screw loosening, breakage, local irritation, and discomfort, are reported for this rigid fixation. 5,18,21,27 Malreduction of syndesmosis has also been noted as a significant problem, and its incidence has been found to be 20.8% to 52% on postoperative CT scans. 9,15,19 The dynamic suture-button technique has increased in popularity because it restores physiological movement while providing more accurate reduction and more satisfactory outcomes than other techniques.…”
Section: Introductionmentioning
confidence: 99%